Development of SED Camera for Quasars in Early Universe (SQUEAN). (4th October 2016) - Kim, Sanghyuk; Jeon, Yiseul; Lee, Hye-In; Park, Woojin; Ji, Tae-Geun; Hyun, Minhee; Choi, Changsu; Im, Myungshin; Pak, Soojong
Abstract: We describe the characteristics and performance of a camera system, Spectral energy distribution Camera for Quasars in Early Universe (SQUEAN). It was developed to measure SEDs of high-redshift quasar candidates (z ≳ 5) and other targets, e.g., young stellar objects, supernovae, and gamma-ray bursts, and to trace the time variability of SEDs of objects such as active galactic nuclei (AGNs). SQUEAN consists of an on-axis focal plane camera module, an autoguiding system, and mechanical supporting structures. The science camera module is composed of a focal reducer, a customizable filter wheel, and a CCD camera on the focal plane. The filter wheel uses filter cartridges that can house filters with different shapes and sizes, enabling the filter wheel to hold 20 filters of 50 mm × 50 mm size, 10 filters of 86 mm × 86 mm size, or many other combinations. The initial filter mask was applied to calibrate the filter wheel with high accuracy, and we verified that the filter position is repeatable at much less than one pixel accuracy. We installed and tested 50 nm medium bandwidth filters of 600–1050 nm and other filters at the commissioning observation in 2015 February. We found that SQUEAN can reach limiting magnitudes of 23.3–25.3 AB mag at 5 σ in a one-hour total integration time.